Factors influencing female students’ choices of Scientific fields: a case study of the university of Ngaoundéré using a stratified survey - Mbelawadzai Joseph; Mbounja Béssémè Fritz; Kouakep Tchaptchié Yannick; Anegue Jean de Dieu (Discover Education)
Abstract In this article, we aim to identify the factors that significantly influence the choice of a scientific or technological field by a female student in the case of the University of Ngaoundéré. By applying a logistic regression model (Logit) to data from a stratified survey, our results highlight the significant negative influence of gender stereotypes and the use of a career counselor on the choice of a purely scientific field by girls. Additionally, it is observed that parental influence plays an important role in the choice of fields. Furthermore, women who have excelled in scientific domains have a considerable impact on the university orientation of young girls in the case of the University of Ngaoundéré. These findings thus underscore the importance of organizing awareness sessions to present to girls the diversity of opportunities that scientific fields offer and to help them overcome the specific obstacles they face, as well as to promote successful female role models.